Epidemiology of Typhoid and Paratyphoid: Implications for Vaccine Policy. (7th March 2019) - Saha, Senjuti; Islam, Md Shfiqul; Sajib, Mohammad Saiful Islam; Saha, Shampa; Uddin, Mohammad Jamal; Hooda, Yogesh; Hasan, Md; Amin, Md Ruhul; Hanif, Mohammed; Shahidullah, Mohammad; Islam, Maksuda; Luby, Stephen P; et al.
Abstract: Background: Typhoid and paratyphoid remain the most common bloodstream infections in many resource-poor settings. The World Health Organization recommends typhoid conjugate vaccines for country-specific introduction, but questions regarding typhoid and paratyphoid epidemiology persist, especially regarding their severity in young children. Methods: We conducted enteric fever surveillance in Bangladesh from 2004 through 2016 in the inpatient departments of 2 pediatric hospitals and the outpatient departments of 1 pediatric hospital and 1 private consultation clinic. Blood cultures were conducted at the discretion of the treating physicians; cases of culture-confirmed typhoid/paratyphoid were included. Hospitalizations and durations of hospitalizations were used as proxies for severity in children <12 years old. Results: We identified 7072 typhoid and 1810 paratyphoid culture-confirmed cases. There was no increasing trend in the proportion of paratyphoid over the 13 years. The median age in the typhoid cases was 60 months, and 15% of the cases occurred in children <24 months old. The median age of the paratyphoid cases was significantly higher, at 90 months ( P < .001); 9.4% were in children <24 months old. The proportion of children (<12 years old) hospitalized with typhoid and paratyphoid (32% and 21%, respectively) decreased with age; there was no significant difference in durations of hospitalizations between age groups. However, children with typhoid were hospitalized for longer than those with paratyphoid. Conclusions: Typhoid and paratyphoid fever are common in Dhaka, including among children under 2 years old, who have equivalent disease severity as older children. Early immunization with typhoid conjugate vaccines could avert substantial morbidity, but broader efforts are required to reduce the paratyphoid burden.